Japanese-Chinese Import Trade Competition During The 1930s Crisis - Nawiyanto, Nawiyanto (UI Scholars Hub, 2009)
In the Indonesian historiography, the contest for market between the Chinese and indigenous traders has long attracted much scholarly attention, however this issue was actually only part of the story. This article seeks to elaborate the Japanese and Chinese import trade competition in Java during the 1930s depression. Drawing upon both primary and secondary historical materials, it is argued that instead of creating a time of hardships, the crisis paved the way for Japan’s import trade expansion. Benefiting from the creation of large market for cheap products among the customers in Java suffering from a decline in purchasing power and their owned trade networks, a great number of Japan products will soon controlle the market. The Chinese found that their well-established economic position was seriously threatened. Although Japan’s fast rising market domination was eventually removed, it was due to the changing of the socio-political environment that created major obstacles for the Japanese to maintain its position, rather than that of the responses of the Chinese traders.